Chemical composition, phytotoxicity and cytogenotoxicity of essential oil from leaves of Psidium guajava L. cultivars (Research, Society and Development, 2021)
Natural products with biological activity, such as essential oils, can be used in the search for and development of ecological herbicides as an alternative to reduce the damage caused by synthetic herbicides. This work to aimed to determine the chemical composition and phytotoxic properties of the essential oils, at concentrations of 3000, 1500, 750, 375 and 187.5 µg/mL, of four cultivars of Psidium guajava (guava) evaluated on germination and root growth of plant models Lactuca sativa and Sorghum bicolor, as well as in the L. sativa cell cycle.  Exposure to essential oils reduced germination and root growth in bioassays, especially at the highest concentration (3000 µg/mL). The essential oils interfered in the normal dynamics of the cell cycle of L. sativa at most concentrations, causing a decrease in the mitotic index and increasing of chromosomal alterations, evidencing aneugenic and clastogenic action. The biological activity of the oils was associated with the presence of sesquiterpenes and monoterpenes found here, such as caryophyllene oxide, (E) -caryophyllene, and limonene. Thus, the essential oils of cultivars of guava demonstrated the promising potential for use as natural herbicides.